2019
DOI: 10.3389/fnins.2019.00378
|View full text |Cite
|
Sign up to set email alerts
|

Role of Leptin in Mood Disorder and Neurodegenerative Disease

Abstract: The critical regulatory role of leptin in the neuroendocrine system has been widely reported. Significantly, leptin can improve learning and memory, affect hippocampal synaptic plasticity, exert neuroprotective efficacy and reduce the risk of several neuropsychiatric diseases. In terms of depression, leptin could modulate the levels of neurotransmitters, neurotrophic factors and reverse the dysfunction in the hypothalamic-pituitary-adrenal axis (HPA). At the same time, leptin affects neurological diseases duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 96 publications
(121 reference statements)
1
49
0
Order By: Relevance
“…Initially famous for its key role as a hormone, regulating body mass homeostasis, with its suppressive effect on food intake and its boosting action on metabolic rate, more recently, leptin's metabolism has been involved in many other processes and diseases [41,42]. This encompasses cancers, due to its pro-carcinogenic effects with action on cell development and suppression of apoptosis, neurodegenerative diseases, by its neuroprotective and neurotrophic effects in Alzheimer's disease, and some mental illnesses, including psychotic and mood disorders [41,42].…”
Section: Leptinmentioning
confidence: 99%
See 2 more Smart Citations
“…Initially famous for its key role as a hormone, regulating body mass homeostasis, with its suppressive effect on food intake and its boosting action on metabolic rate, more recently, leptin's metabolism has been involved in many other processes and diseases [41,42]. This encompasses cancers, due to its pro-carcinogenic effects with action on cell development and suppression of apoptosis, neurodegenerative diseases, by its neuroprotective and neurotrophic effects in Alzheimer's disease, and some mental illnesses, including psychotic and mood disorders [41,42].…”
Section: Leptinmentioning
confidence: 99%
“…Modifications of leptin metabolism and its gene expression, as well as its receptor, have been reported among patients with mental health disorders, independently to psychotropic drugs or in absence of antipsychotics [43]. Several studies showed a particular interest in the relationship between leptin and depressive disorders, but with discordant conclusions [42][43][44][45].…”
Section: Leptin and Psychiatric Illnessesmentioning
confidence: 99%
See 1 more Smart Citation
“…This data are supported by the observation that administration of leptin exerts an antidepressant-like effect [ 91 ], through dopaminergic neurotransmission regulation in mesolimbic areas [ 92 ]. In particular, leptin reduces symptoms of depression and has an anxiolytic effect affecting the HPA [ 93 , 94 ], and stimulating brain-derived neurotrophic factor (BDNF) production and function [ 95 , 96 , 97 ]. In addition, the deletion of leptin receptor (LepRb) and its downregulation are associated with depression-like behavioral impairments, indicating that leptin-lepRb signaling is involved in the molecular mechanism of leptin antidepressant action [ 98 , 99 ].…”
Section: Adipokinesmentioning
confidence: 99%
“…Leptin and ghrelin have also been implicated in neuropsychiatric disorders [ 30 , 31 , 32 ] and might lie at the very crossroads between obesity and mood. Therefore, they are of special interest in regard to FC in affective disorders.…”
Section: Introductionmentioning
confidence: 99%